If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = -2x * 27 Reorder the terms for easier multiplication: 3 = -2 * 27x Multiply -2 * 27 3 = -54x Solving 3 = -54x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '54x' to each side of the equation. 3 + 54x = -54x + 54x Combine like terms: -54x + 54x = 0 3 + 54x = 0 Add '-3' to each side of the equation. 3 + -3 + 54x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 54x = 0 + -3 54x = 0 + -3 Combine like terms: 0 + -3 = -3 54x = -3 Divide each side by '54'. x = -0.05555555556 Simplifying x = -0.05555555556
| 3x-2x+9x=0 | | n-15=35 | | 3(5x-2)=11 | | (3x+4)(x-1)+54=0 | | 3x+c=300 | | 5sin(x)=2cos(x) | | X*3+2x=42 | | -3+5/3x=4 | | 3x+7=379 | | W=5x+2 | | 40+a=2(16+a) | | Y=200x-80 | | 3x+8y=39 | | 4x+2=1/2x+17 | | 0.5x+5=4(0.5x-5) | | 4x-4+x=5x-4 | | 2.5y+y=56 | | x+3+2x=3x+2 | | 3(6+5)-10=3+3(6)+2 | | 2*49+x*(-7)-3=140 | | 2*36+x*(-6)-3=140 | | X^5+6x^3+x=0 | | 2*9+x*(3)-3=140 | | 3(4+2)=2(4)+14-4 | | 2*4+x*(2)-3=140 | | 2*25+x*(5)-3=140 | | 4(d+5)=16 | | 10-10*2= | | 10*2-10= | | 2*25+x*(-5)-3=140 | | 2*9+x*(-3)-3=140 | | 2*4+x*(-2)-3=140 |